Construction of a model of subsoil moisture movement in cultivated slope lands - Andrey A. Mikhaylin (Аграрная наука Евро-Северо-Востока, 2025)
Insufficient study of the dynamics of moisture movement both in the soil loosened by the tillage tool and in the zone of uncultivated subsoil wall in the conditions of moisture deficient south of Russia necessitated for development of a mathematical model of subsoil moisture transfer. A distinctive feature of this model is the study of moisture transfer in the zone of the upper soil layer of 0.60 m by the developed universal tillage tool for cultivating of sloping and plain lands. To study the moistening process in the slope soil layer treated by the new method, the following assumptions were made: the soil skeleton was geometrically unchanged; hysteresis was excluded in the system under consideration; the moisture inside the soil was not compressed; the air pressure inside the treated soil horizon was equal to the atmospheric pressure; capillary and gravitational phenomena were the main causes of moisture movement inside the treated layer; subsoil moisture transfer was related to isothermal processes; the Cartesian coordinate system was used, and the z-axis was directed vertically upwards. These assumptions made it possible to consider in the model of subsoil moisture movement only the dynamics of capillary forces and sorption occurring due to soil moistening. As the result, a mathematical model of subsoil moisture transfer was proposed on the basis of the Navier-Stokes equation for water movement in a porous medium. This let to determine the main parameters of the moisture transfer dynamics in the layer under consideration: the coefficients of diffusivity, moisture conductivity and capillary absorption capacity. At the same time, a computer program was developed to solve the boundary value problem of dynamics – subsoil moisture transfer on a slope, taking into account the heterogeneous structures obtained during soil treatment using a new method.